1996
DOI: 10.1183/09031936.96.09112371
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moderate alcohol consumption on obstructive sleep apnoea with and without AutoSet nasal CPAP therapy

Abstract: I In nf fl lu ue en nc ce e o of f m mo od de er ra at te e a al lc co oh ho ol l c co on ns su um mp pt ti io on n o on n o ob bs st tr ru uc ct ti iv ve e s sl le ee ep p a ap pn no oe ea a w wi it th h a an nd d w wi it th ho ou ut t A Au ut to oS Se et t " " n na as sa al l C CP PA AP P t th he er ra ap py y Fourteen adult males with untreated OSAS but without heart or lung disease were studied (age 53±9 yrs, body mass index (BMI) 33±5 kg·m -2 (mean±SD). The subjects underwent overnight polysomnography on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
8

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 17 publications
(28 reference statements)
0
32
0
8
Order By: Relevance
“…kg BW -1 did not alter respiration during sleep. TESCHLER et al [14] suggested similar doses did not alter pressure requirements to maintain ventilation during sleep in patients with severe OSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…kg BW -1 did not alter respiration during sleep. TESCHLER et al [14] suggested similar doses did not alter pressure requirements to maintain ventilation during sleep in patients with severe OSA.…”
Section: Discussionmentioning
confidence: 99%
“…kg BW -1 ), the effects upon apnoea severity are less clear. Some authors report an increase [9,12,27] and others no effect [13,14] upon severity of OSA. BERRY et al [10] reported 0.5 g alcohol .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Block et al (13) found no difference in the AHI (2.8 to 3.0 events/h) when subjects, with milder OSA, were given 1 g alcohol/kg BW (BAC 0.075 g/dl). Similarly, Teschler et al (14) found no difference in the AHI (44-51 events/h) when males with severe OSA were given 0.5 g alcohol/kg BW (BAC 0.05 g/dl). To further understand the effects of alcohol on sleepdisordered breathing, we undertook this study to determine the effects of moderate alcohol consumption on apnea-hypopnea frequency in healthy middle-aged male subjects.…”
Section: Introductionmentioning
confidence: 92%
“…Did he/she sleep on his back? Was the drug and alcohol level [15], degree of somnolence, and state of the nasal airway typical? Did he/she have bronchospasm?…”
mentioning
confidence: 99%